Faktor-Faktor yang Berhubungan dengan Penggunaan Alat Kontrasepsi Dalam Rahim di UPTD Puskesmas Lubuk Rukam OKU Tahun 2021 - Marita Marita; Chairuna Chairuna; Hazairin Effendi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Intra Uterine Devices (IUD) is a small contraceptive devices that is put into the uterus (womb) wich is very effective, reversible and long lasting to prevent pregnancy, and it can be used by all women in their productive age. Intra Uterine Devices can last for 10 years. National target achievement of IUD acceptors is 23,1%. This study was aimed to find out the correlation between age, education and parity with the use of Intra Uterine Devices (IUD) at Lubuk Rukam Public Health Center Peninjauan Districs Ogan Komering Ulu Regency Year 2021. This study applied survey analytical method using cross sectional design. The Population of this study was taken from all active family planning program at Lubuk Rukam Public Health Center year 2021 with a total of 1861 acceptors. Ther ewere 330 respondents taken as the samples who were chosen by applying systematic random sampling method. The data were then analysed using chi square statistics. The result showed that the factors which showed correlation with Intra Uterine Devices were education with p-Value = 0,006 (≤ 0,05), and parity with p-Value = 0,0210 (≤ 0,05), meanwhile, the factor which did not show correlation with Intra Uterine Devices was age with a p-Value = 0,162(>0,05). This study can be used as the reference to add insight and skills for readers and a reference to make the policy dealing with family planning in Public Health Center.